2020
DOI: 10.1183/23120541.00168-2020
|View full text |Cite
|
Sign up to set email alerts
|

The airway microbiota and exacerbations of COPD

Abstract: AimThe aim of this study was to investigate whether the compositionality of the lower airway microbiota predicts later exacerbation risk in persons with COPD in a cohort study.Materials and methodsWe collected lower airways microbiota samples by bronchoalveolar lavage and protected specimen brushes, and oral wash samples from 122 participants with COPD. Bacterial DNA was extracted from all samples, before we sequenced the V3-V4 region of the 16S RNA gene. The frequency of moderate and severe COPD exacerbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…In our study, the most abundant phyla ( Firmicutes and Bacteroidetes ) were shared by IPF and COPD patients, while Actinobacteria and Proteobacteria were the third most abundant phyla in the respective study groups. This is coherent with other studies [ 6 , 31 34 ]. The most abundant genera in our study were Streptococcus , Rothia , Veillonella and Prevotella , which are described earlier for IPF patients, but also in other chronic pulmonary diseases [ 29 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…In our study, the most abundant phyla ( Firmicutes and Bacteroidetes ) were shared by IPF and COPD patients, while Actinobacteria and Proteobacteria were the third most abundant phyla in the respective study groups. This is coherent with other studies [ 6 , 31 34 ]. The most abundant genera in our study were Streptococcus , Rothia , Veillonella and Prevotella , which are described earlier for IPF patients, but also in other chronic pulmonary diseases [ 29 , 35 ].…”
Section: Discussionsupporting
confidence: 94%
“…The altered microbiota has an impact on respiratory diseases as well. Many studies indicated that patients with allergy, asthma, and chronic obstructive pulmonary disease (COPD) have disturbed the microbiome composition, which can accelerate the further pathological processes ( Choi et al, 2014 ; Huang, 2015 ; Depner et al, 2017 ; Leiten et al, 2020 ). Asthmatic patients differ in the microbiota composition as well, and it seems to be linked with the phenotype of the disease.…”
Section: Microbiome Of the Respiratory Tractmentioning
confidence: 99%
“…Participants were recruited from our outpatient clinic at the Department of Thoracic Medicine, Haukeland University Hospital, Norway, participating in The Microbiome in Interstitial Lung Disease study (MicroILD) [16] and The Bergen Chronic Obstructive Pulmonary Disease Microbiome study (MicroCOPD) [17]. All study participants were examined in one center with consistent methodology by the same investigators.…”
Section: Methodsmentioning
confidence: 99%